A pilot study of a therapeutic workplace in women arrested for prostitution. (23rd August 2022) - DeFulio, Anthony; Cosottile, David W.; Devoto, Amanda; Silverman, Kenneth
Abstract: People with substance use disorder who have been arrested for prostitution are likely to require intensive interventions to increase drug abstinence and reduce HIV risk behaviors. The Therapeutic Workplace (TW) may be ideal for this population, because it combines contingency management for drug abstinence and paid job training. This study was a preliminary evaluation of the TW intervention in opioid dependent women arrested for prostitution. Participants ( N  = 37) were randomly assigned to a specialized diversion program, or the diversion program plus the TW for 4 months. Group comparisons showed no difference in drug use. However, analysis of drug use relative to the onset of drug abstinence contingencies in the TW group showed greater abstinence during the implementation period, with a significant difference for opioids ( p  = 0.046). The pre‐post contingency outcomes provide preliminary evidence that the TW could promote drug abstinence in people involved in the criminal justice system who attend paid job training.